The Financing Health System Problem in Algeria - Mohammed, Ali Dehmene (International Research Journal of Management, IT & Social Sciences, 2016)
The health sector in Algeria witnesses a great development, especially during the last two decades of the last century to coincide with the economic and social changes of the country. But despite the enormity of what the state spends on this sensitive sector in order to meet the growing demand for health services provided by the public or private sector, which, however, take advantage of these services was still below the required level where the sector remains vulnerable to various problems